Understanding the Molecular Basis of Fragile X Syndrome Using Differentiated Mesenchymal Stem Cells - Fazeli, Zahra; Ghaderian, Sayyed Mohammad Hossein; Najmabadi, Hossein; Omrani, Mir Davood (Iranian Journal of Child Neurology, 2022)
Abstract Objectives Fragile X syndrome (FXS) has been known as the most common cause of inherited intellectual disability and autism. This disease results from the loss of fragile X mental retardation protein expression due to the expansion of CGG repeats located on the 5’ untranslated region of the fragile X mental retardation 1 (FMR1) gene. Materials & Methods In the present study, the peripheral blood-mesenchymal stem cells (PB-MSCs) of two female full mutation carriers were differentiated into neuronal cells by the suppression of bone morphogenesis pathway signaling. Then, the expression of genes adjacent to CGG repeats expansion, including SLIT and NTRK-like protein 2 (SLITRK2), SLIT and NTRK-like protein 4 (SLITRK4), methyl CpG binding protein 2 (MECP2), and gamma-aminobutyric acid receptor subunit alpha-3 (GABRA3), were evaluated in these cells using SYBR Green real-time polymerase chain reaction. Results The obtained results indicated that the expression of SLITRK2 and SLITRK4 were upregulated and downregulated in the neuron-like cells differentiated from the PB-MSCs of females with FMR1 full mutation, compared to that of the normal females, respectively. Furthermore, the expression of MECP2 and GABRA3 genes were observed to be related to the phenotypic differences observed in the female FMR1 full mutation carriers Conclusion The observed association of expression of genes located upstream of the FMR1 gene with phenotypic differences in the female carriers could increase the understanding of novel therapeutic targets for patients with mild symptoms of FXS and the patients affected by other FMR1-related disorders